2024
DOI: 10.2147/ppa.s457255
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health-Related Quality of Life Following Root Canal Treatment of First Permanent Molars Among Children. A Cross-Sectional Study

Nada Bamashmous,
Wala Dhafar,
Jihan Turkistani
et al.

Abstract: Aim This study aimed to assess the Oral Health-Related Quality of Life (OHRQoL) of pediatric patients (9–18 years old) who underwent root canal treatment (RCT) on first permanent molars (FPMs). Methods A cross-sectional study was conducted at three healthcare centers in Jeddah, Saudi Arabia. Participants (n = 482) completed the validated OHIP5-Ar questionnaire to assess OHRQoL. Responses were classified as “optimal” (no problems) or “less than optimal” (any reported pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In this research, Nada Othman Bamashmous et al found that there was no significant relationship between optimal OHRQoL and gender, family income, and location of the tooth being treated, however treating one FPM with root canal treatment (RCT) provided an opportunity to increase optimal OHRQoL. 1 However, it should be noted that in children, dental caries lesions in the anterior and posterior segments will have a greater impact on posterior teeth after OHRQoL. In addition, the greater number of teeth affected by carious lesions in early childhood will have a negative impact on OHRQoL over time.…”
Section: Dear Editormentioning
confidence: 79%
See 3 more Smart Citations
“…In this research, Nada Othman Bamashmous et al found that there was no significant relationship between optimal OHRQoL and gender, family income, and location of the tooth being treated, however treating one FPM with root canal treatment (RCT) provided an opportunity to increase optimal OHRQoL. 1 However, it should be noted that in children, dental caries lesions in the anterior and posterior segments will have a greater impact on posterior teeth after OHRQoL. In addition, the greater number of teeth affected by carious lesions in early childhood will have a negative impact on OHRQoL over time.…”
Section: Dear Editormentioning
confidence: 79%
“…We have read the paper written by Nada Othman Bamashmous et al about Oral Health-Related Quality of Life Following Root Canal Treatment of First Permanent Molars Among Children. 1 We congratulate all authors who have provided information about the importance of maintaining First permanent molars (FPM) which play an important role in mastication and facial development, especially in children. First permanent molars are closely related to dental health and are an important parameter that determines oral health.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations